KOMPETENSI PROFESIONAL GURU TERHADAP HASIL BELAJAR - Nufiar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
Professional competence is a knowledge that must be possessed by every teacher, so that in the teaching and learning process, teachers will be more effective and efficient in teaching in the classroom and students will easily understand the material explained by the teacher. Professional emphasizes the mastery of science or management ability and its implementation strategy, professional is not just knowledge of technology and management but is more of an attitude, professional development is more than a technician not only has high skills but has the required behavior